Geometry, Algebra, Number Theory, and Their Information Technology Applications : Toronto, Canada, June, 2016, and Kozhikode, India, August, 2016 /: Toronto, Canada, June, 2016, and Kozhikode, India, August, 2016. (2018) - Unknown
No abstract available